SIMULTANEOUS DEBULKING OF GREAT OMENTUM LIKE A PALLIATIVE STAGE OF METABOLIC SYNDROM AND OBESITY TREATMENT = СИМУЛЬТАННИЙ ДЕБАЛКІНГ ЧЕПЦЯ ЯК ПАЛІАТИВНИЙ ЕТАП ЛІКУВАННЯ МЕТАБОЛІЧНОГО СИНДРОМУ І ОЖИРІННЯ - Mylytsya, K. M.; Lavryk, A. S.; Lavryk, O. A. (Journal of Education, Health and Sport, 2016)
Mylytsya К. M., Lavryk А. S., Lavryk О. А. SIMULTANEOUS DEBULKING OF GREAT OMENTUM LIKE A PALLIATIVE STAGE OF METABOLIC SYNDROM AND OBESITY TREATMENT = СИМУЛЬТАННИЙ ДЕБАЛКІНГ ЧЕПЦЯ ЯК ПАЛІАТИВНИЙ ЕТАП ЛІКУВАННЯ МЕТАБОЛІЧНОГО СИНДРОМУ І ОЖИРІННЯ. Journal of Education, Health and Sport. 2016;6(9):691-698. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.159095 http://ojs.ukw.edu.pl/index.php/johs/article/view/3896 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.09.2016. Revised 24.09.2016. Accepted: 24.09.2016. SIMULTANEOUS DEBULKING OF GREAT OMENTUM LIKE A PALLIATIVE STAGE OF METABOLIC SYNDROM AND OBESITY TREATMENT К. M. Mylytsya1, А. S. Lavryk2, О. А. Lavryk2 1State Institution “Zaporizhia Medical Academy of Post-Graduate Education Ministry of Health of Ukraine” 2Shalimov National Institute of Surgery and Transplantology of NAMS of Ukraine Summary The article discusses the possibility and expediency of simultaneous visceral fat debulking (omentectomy) in patients with metabolic syndrome and obesity. The investigation of the level index HOMA in the pre- and postoperative period in 50 patients with metabolic syndrome and obesity. Of these various 25 performed abdominal surgery, the rest of the 25 performed similar operations with simultaneous omentectomy. Results indicate that the greater omentum debulking affect carbohydrate metabolism by reducing the severity of insulin resistance and hyperinsulinemia. Key words: debulking, greater omentum, metabolic syndrome, obesity, simultaneous surgery. СИМУЛЬТАННЫЙ ДЕБАЛКИНГ БОЛЬШОГО САЛЬНИКА КАК ПАЛЛИАТИВНЫЙ ЭТАП ЛЕЧЕНИЯ МЕТАБОЛИЧЕСКОГО СИНДРОМА И ОЖИРЕНИЯ К. Н. Милица1, А. С. Лаврик2, О. А. Лаврик2 1 ГУ «Запорожская медицинская академия последипломного образования МЗ Украины», 2Национальный институт хирургии и трансплантологии имени А.А. Шалимова НАМН Украины, Киев Резюме В статье обсуждаются вопросы возможности и целесообразности применения симультанного дебалкинга висцеральной жировой ткани в виде оментэктомии у пациентов с метаболическим синдромом и ожирением. Проведено исследование уровня индекса HOMA в до- и послеоперационном периоде у 50 пациентов с метаболическим синдромом и ожирением. У 25 пациентов выполнены различные абдоминальные операции, у остальных − подобные операции с симультанной оментэктомией. Результаты указывают на то, что дебалкинг большого сальника влияет на углеводный обмен за счет снижения выраженности гиперинсулинемии и инсулинорезистентности. Ключевые слова: дебалкинг, большой сальник, метаболический синдром, ожирение, симультанная хирургия. СИМУЛЬТАННИЙ ДЕБАЛКІНГ ЧЕПЦЯ ЯК ПАЛІАТИВНИЙ ЕТАП ЛІКУВАННЯ МЕТАБОЛІЧНОГО СИНДРОМУ І ОЖИРІННЯ К. М. Милиця1, А. С. Лаврик2, О. А. Лаврик2 1 ДЗ «Запорізька медична академія післядипломної освіти МОЗ України», 2 Національний інститут хірургії та трансплантологiї імені О. О. Шалімова НАМН України, Київ Резюме У статті обговорюються питання можливості і доцільності застосування симультанного дебалкінга вісцеральної жирової тканини у вигляді оментектомії у пацієнтів з метаболічним синдромом та ожирінням. Проведено дослідження рівня індексу HOMA в до- і післяопераційному періоді у 50 пацієнтів з метаболічним синдромом та ожирінням. У 25 пацієнтів виконані різні абдомінальні операції, у інших – подібні операції з симультанною оментектомією. Результати вказують на те, що дебалкінг великого чепця впливає на вуглеводний обмін за рахунок зниження вираженості гіперінсулінемії і інсулінорезистентності. Ключові слова: дебалкінг, великий чепець, метаболічний синдром, ожиріння, симультанна хірургія.